A structure-based approach towards the identification of novel antichagasic compounds: Trypanosoma cruzi carbonic anhydrase inhibitors. (1st January 2020) - Llanos, Manuel A.; Sbaraglini, María L.; Villalba, María L.; Ruiz, María D.; Carrillo, Carolina; Alba Soto, Catalina; Talevi, Alan; Angeli, Andrea; Parkkila, Seppo; Supuran, Claudiu T.; Gavernet, Luciana
Abstract: Trypanosoma cruzi carbonic anhydrase ( Tc CA) has recently emerged as an interesting target for the design of new compounds to treat Chagas disease. In this study we report the results of a structure-based virtual screening campaign to identify novel and selective Tc CA inhibitors. The combination of properly validated computational methodologies such as comparative modelling, molecular dynamics and docking simulations allowed us to find high potency hits, with KI values in the nanomolar range. The compounds also showed trypanocidal effects against T. cruzi epimastigotes and trypomastigotes. All the candidates are selective for inhibiting Tc CA over the human isoform CA II, which is encouraging in terms of possible therapeutic safety and efficacy.